2004
DOI: 10.1210/me.2004-0194
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uncoupling Protein 1 in the Metabolism and Adiposity of RIIβ-Protein Kinase A-Deficient Mice

Abstract: Mice lacking the RII beta regulatory subunit of protein kinase A exhibit a 50% reduction in white adipose tissue stores compared with wild-type littermates and are resistant to diet-induced obesity. RII beta(-/-) mice also have an increase in resting oxygen consumption along with a 4-fold increase in the brown adipose-specific mitochondrial uncoupling protein 1 (UCP1). In this study, we examined the basis for UCP1 induction and tested the hypothesis that the induced levels of UCP1 in RII beta null mice are ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…This study also analyzed Prkar2b K/K ;Ucp1 K/K double KO mice, which retained the lean phenotype. This observation demonstrated that induction of UCP1 and increased resting oxygen consumption are not the cause of leanness in the Prkar2b K/K mice (Nolan et al 2004). In addition to this, experiments using leptin-deficient Lep ob/ob mice showed that the KO of Prkar2b provided substantial rescue of the obese phenotype.…”
Section: Prkar2b Kosmentioning
confidence: 77%
“…This study also analyzed Prkar2b K/K ;Ucp1 K/K double KO mice, which retained the lean phenotype. This observation demonstrated that induction of UCP1 and increased resting oxygen consumption are not the cause of leanness in the Prkar2b K/K mice (Nolan et al 2004). In addition to this, experiments using leptin-deficient Lep ob/ob mice showed that the KO of Prkar2b provided substantial rescue of the obese phenotype.…”
Section: Prkar2b Kosmentioning
confidence: 77%
“…βAR-stimulated lipolysis is impaired but the basal rate of lipolysis is increased in the WAT of Riiβ-knockout mice (Planas et al 1999). In BAT, RIIβ deficiency leads to increases in mitochondrial content and thermogenesis (Nolan et al 2004, Newhall et al 2005. However in human, obesity is associated with reduced RIIβ expression and PKA activity in WAT (Mantovani et al 2009).…”
Section: Camp/pka In Adipose Tissuesmentioning
confidence: 99%
“…We previously reported that RΙΙβ KO mice had increased resting oxygen consumption (VO 2 /total body weight), which we hypothesized was related to their elevated basal metabolism and lean phenotype (1,6). To further assess the physiological impact of RIIβ deficiency on metabolism, RIIβ lox/lox animals were subjected to metabolic monitoring for two consecutive days with free access to food and water.…”
Section: Metabolic Analysis Of Mice Engineered To Reexpress Riiβ In Smentioning
confidence: 99%
“…These mice have an extended lifespan and show diminished age-related metabolic dysfunctions such as fatty liver and insulin resistance (3). Compared with their WT littermates, RIIβ KO mice have normal to slightly increased food intake, a twofold increase in nocturnal physical activity, and a basal metabolic rate (VO 2 consumption) that is higher than WT if calculated based on total body weight (4)(5)(6). RIIβ is highly expressed in the mouse CNS, brown adipose tissue (BAT), and WAT with limited expression elsewhere (1,(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation